ショウワ キチ ニオケル ジフブキ ハッセイチュウ ノ シテイ ト フウソク ノ カンケイ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 真木, 太一; マキ, タイチ; MAKI, Taichi (国立極地研究所, 1971)
P(論文) At Syowa Station, Antarctica the author investigated the relation between the visibility and the wind velocity from May to August in 1970. On some occasions, blowing snow was mixed in snow fall. The results are summarized as follows The snow particles start to drift when the wind velocity at 10m height (U_<10>) becomes larger than 8m/s and the visibility becomes 150m with the wind velocity of about 15m/s 10m at about 25m/s and 2～3m at about 35m/s. The visibility observed at 1.5m height (V) is inversely proportional to the fifth power of the wind velocity : log (1/V) =5.00×logU_<10>-8.03, where V and U_<10> denote MKS unit. The deduction of friction drag (τ-τ_c) is almost proportional to the fifth power of the velocity (U_<10>). log (τ-τ_c) =5.10×logU_<10>-7.34, where τ is obtained from the friction velocity (U_*), and τ_c from the roughness length (Z_0) of the constant value of 0.01cm. τ, τ_c and U_<10> denote MKS unit. τ, τ_c is related to the energy which causes the blowing of snow particles and is almost inversely proportional to the visibility. departmental bulletin paper